Large electrocaloric strength and broad electrocaloric temperature span in lead-free Ba0.85Ca0.15Ti1−xHfxO3ceramics. Issue 10 (17th January 2017) - Wang, Xiangjian; Wu, Jiagang; Dkhil, Brahim; Zhao, Chunlin; Li, Tangyuan; Li, Wei; Lou, Xiaojie
Abstract : The electrocaloric (EC) effect of Ba0.85 Ca0.15 Ti1− x Hf x O3 (abbreviated as: BCTH x ) ceramics has been systematically investigated using an indirect method. Abstract : The electrocaloric (EC) effect of Ba0.85 Ca0.15 Ti1− x Hf x O3 (abbreviated as: BCTH x ) ceramics has been systematically investigated using an indirect method. Our results indicate that the BCTH0.06 ceramic exhibits a sharp ferroelectric–paraelectric phase transition, around which a large EC value of 1.03 K is obtained under the electric field of 35 kV cm −1, associated with a relatively broad electrocaloric temperature span. The giant EC strength of the BCTH0.06 ceramic is 0.29–0.31 K mm kV −1 under an external electric field of 9 to 35 kV cm −1, which is larger than most previous values. The temperature of the EC peak shifts to higher temperature as the electric field increases, which implies that electric field may be another powerful tool to obtain a large EC value and modulate the EC peak. The ceramics with higher Hf contents display a strong diffusive character. The BCTH0.15 ceramic shows a relatively small EC strength (0.10–0.13 K mm kV −1 ) with a broader EC temperature span. The diffusive feature of the BCTH x ceramics with high Hf concentrations broaden the electrocaloric temperature span and meanwhile decrease the EC strength considerably. Our results indicate that compositional modification in BaTiO3 -based ceramics offers a promising route for designing potential dielectric cooling materials with excellent EC properties.